Manipulating Cellular Factors to Combat Viruses: A Case Study From the Plant Eukaryotic Translation Initiation Factors eIF4 - Schmitt-Keichinger, Corinne (Frontiers in Microbiology, 2019)
Genes conferring resistance to plant viruses fall in two categories; the dominant genes that mostly code for proteins with a nucleotide binding site and leucine rich repeats (NBS-LRR), and that directly or indirectly, recognize viral avirulence factors (Avr), and the recessive genes. The latter provide a so-called recessive resistance. They represent roughly half of the known resistance genes and are alleles of genes that play an important role in the virus life cycle. Conversely, all cellular genes critical for the viral infection virtually represent recessive resistance genes. Based on the well-documented case of recessive resistance mediated by eukaryotic translation initiation factors of the 4E/4G family, this review is intended to summarize the possible approaches to control viruses via their host interactors. Classically, resistant crops have been developed through introgression of natural variants of the susceptibility factor from compatible relatives or by random mutagenesis and screening. Transgenic methods have also been applied to engineer improved crops by overexpressing the translation factor either in its wild type form or after directed mutagenesis. More recently, innovative approaches like silencing or genome editing have proven their great potential in model and crop plants. The advantages and limits of these different strategies are discussed. This example illustrates the need to identify and characterize more host factors involved in virus multiplication and to assess their application potential in the control of viral diseases.